[Obras seleccionadas] : Le fabbriche e i disegni di Andrea Palladio e le terme romane (s.n., 2023)
Teatro Olímpico, Plaza Matteotti (Vicenza) - Palacio Porto-Festa (Vicenza) - Palacio Chiericati, Plaza Matteotti (Vicenza) - Palacio Thiene (Vicenza) - Palacio della Ragione, Basilica (Vicenza) - Pequeña casa Valmarana - Villa La Rotonda (Vicenza) - Villa Godi, Lonedo, Lugo (Vicenza) - Villa Poiana, Poiana Maggiore (Vicenza) - Villa Foscari -Malcontenta-, Malcontenta (Venecia) - Villa Trissino-Facchini, Meledo (Vicenza) - Villa Sarego, Miega - Villa Thiene, Cicogna (Padua) - Villa Emo, Fanzolo di Vedelago (Treviso) - Villa Barbaro, Maser (Treviso) - Iglesia del Redentore, Rio della Croce (Venecia) - Iglesia San Giorgio Maggiore, Isla de San Giorgio (Venecia) - Iglesia de Santa Lucia (Venecia) - San Francesco della Vigna -fachada- (Venecia)